Dr Darko Dimovski "Hate crime", Center for publication, Faculty of Law, University of Niš,Niš, 2020 - Mirić, Filip (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Hate crime is a very old social phenomenon. These crimes follow human history because the feeling of hatred is one of the basic feelings. Criminologically and criminal law speaking, these are criminal acts with elements of violence, which differ from other criminal acts in that they were committed due to the existence of prejudice against the victim. Until now, this form of crime has not been the subject of comprehensive studies in the Serbian criminological literature. Prof. dr Darko Dimovski successfully eliminated this lack of literature, with his monograph titled "Hate Crime" published by the Center for Publications of the Faculty of Law, University of Niš.